Cover Image. (3rd December 2019) - Lang, Rong; Goldberg, Stefanie; Blagodatsky, Sergey; Piepho, Hans‐Peter; Harrison, Rhett D.; Xu, Jianchu; Cadisch, Georg
Abstract : The cover image is based on the Research Article Converting forests into rubber plantations weakened the soil CH4 sink in tropical uplands by Rong Lang et al., https://doi.org/10.1002/ldr.3417 .